Motor learning in lucid dreams: quantitative and qualitative investigations - Schädlich, Melanie (2017)
In sports practice a well-established method is mental practice which is, for example, applied in elite sports to intensify practice and to offer additional practice sessions when opportunities for physical practice are limited (Erlacher, 2007). It is also used on other areas, such as surgery and music. There is a special way of mentally rehearsing movements without physical activity: in our dreams (Stumbrys, 2014). In so called lucid dreams, the dreamer is consciously aware that he or she is dreaming and can thus decide to carry out actions deliberately (Schredl & Erlacher, 2004). In a survey by Erlacher, Stumbrys, and Schredl (2011–2012) it was shown that within a German sample 9% of all athletes who had lucid dreams used the lucid dream state to practice motor skills, for most of them with a positive impact on physical performance. Furthermore, anecdotal examples and previous qualitative and quantitative research has demonstrated that practicing movements in lucid dreams is possible and could possibly even improve performance in waking life for (overview see e.g. Stumbrys, 2014). However, the effectiveness of lucid dream practice had not yet been studies in a controlled sleep laboratory setting. The aim of this investigation was to further explore the effectiveness of lucid dream practice, and to derive practical implications for athletes. A particular goal was to assess the effectiveness of lucid dream practice using signal verified lucid dreams in a sleep laboratory. Furthermore, an extensive qualitative interview study was intended to explore the potential as well as phenomenal experience and difficulties of lucid dream practice. A similar study was planned for musicians to investigate if lucid dream practice can also be applied in this area. Since a requirement for lucid dream practice is to actually achieve lucidity in the dream state, another goal of this investigation was to test two ways of lucid dream induction by external stimulation. The first chapter of this dissertation gives an introduction into mental practice, including evidence that mental practice can improve physical performance in sport and other areas, such as music education. The second chapter first provides some information on sleep and dreams, followed by characteristics and applications of lucid dreams. Chapter three addresses lucid dream induction. The attached book chapter includes a detailed description and evaluation of induction techniques and discusses research problems. Then a study on lucid dream induction through visual and tactile stimulation is presented (Paper 1). Chapter four contains the most important contributions of this investigation: After introducing lucid dream practice, a sleep laboratory study is outlined which investigated the effectiveness of lucid dream practice using a dart throwing task (Paper 2). Then an extensive qualitative study is presented in which 16 athletes were interviewed about their experiences with lucid dream practice (Paper 3), followed by a smaller pilot study in which the potential of lucid dream practice for musicians was explored (Paper 4). Finally, in the last chapter the findings of all studies are summarized and discussed, deriving implications for both sports practice and future research.
Publikationsbasierte Dissertation
Keywords: Hochschulschrift; Motorik; Lernen; Musik; Sport; Mentales Training; Traumbewusstsein; Motorisches Lernen